Effects of feed-withdrawal time on finishing-pig carcass characteristics and economics in a commercial environment - H L Frobose; L N Edwards; K J Prusa; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2010)
The effects of feed-withdrawal time on finishing-pig carcass composition and net returns were determined in 2 studies. In Exp. 1, a total of 728 pigs (BW = 286.4 ± 2.7 lb, 10 to 19 pigs per pen) were marketed from 48 pens that were randomly assigned to 1 of 4 treatments: feed withdrawal times of 7, 24, 36, or 48 h before harvest. Pigs were fed a common corn-soybean meal diet containing dried distillers grains with solubles (DDGS) and bakery co-products. As expected, increased feed withdrawal time decreased (linear; P<0.001) live weight. Withholding feed also decreased (linear; P<0.03) HCW and backfat depth. Percentage yield increased (quadratic; P<0.01) with longer withdrawal periods, as did percentage lean (linear; P<0.01). Withholding feed increased (quadratic; P<0.01) live price and, accordingly, also increased (linear; P<0.001) carcass price. These results were due in part to increased (linear; P<0.02) premiums and decreased (linear; P<0.01) weight discounts. Total value and net revenue received were similar (P>0.32) between treatments as HCW decreased in fasted pigs, but feed intake per pig also decreased (quadratic; P 0.22) in HCW, percentage lean, or backfat depth across treatments. However, as in Exp.1, percentage yield (linear; P<0.001) increased with increasing withdrawal time. Although withholding feed had no effect (P>0.31) on the incidence of runny bung, it did increase (linear; P<0.001) the incidence of leaking ingesta. For economics, as in Exp. 1, withholding feed increased (linear; P<0.002) live price. Additionally, pigs that were fasted had increased (quadratic; P<0.05) carcass price. Although premiums were similar (P>0.32) across treatments, withholding feed decreased (quadratic; P<0.04) weight discounts. Total value and net revenue received per pig were similar (P>0.88) across treatments, but withholding feed decreased (linear; P<0.001) feed intake, resulting in feed savings of up to $0.46/pig. Overall, withholding feed can be used to avoid weight discounts in heavyweight pigs without negatively impacting carcass composition and maintaining overall revenue per pig. However, these advantages come with a potential reduction in carcass weight and increased incidence of leaking ingesta, which can result in condemned heads at inspection and losses of $3 to 4 per carcass.; Swine Day, Manhattan, KS, November 18, 2010
Keywords: Swine Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-016-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1038; Swine; Carcass; Fasting; Feed withdrawal